Didactical Transposition in Designing Social Arithmetic Learning Vlogs in Tijarah Context - Liana Septy; Agustiany Dumeva Putri; Yuli Fitrianti; Feli Ramury (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2024)
Change of thinking starting from the references used to new knowledge that will be taught and learned. In every design or learning process there will definitely be a didactic transposition process. This research is a phenomenological research that explains what didactic transpositions occurred when designing the arithmetic learning vlog script in the Tijarah context which was prepared by one of the students at UIN Raden Fatah Palembang. The data used is in the form of learning resources, results of expert discussions and 4 drafts of arithmetic learning vlog scripts in the Tijarah context. All data is explained and combined into a table that is easier to understand. Data collection took the form of group discussions and also portfolio analysis carried out on learning vlog scripts. From the results of the analysis, it was found that didactic transposition occurred in the preparation of the Arithmetic learning vlog script in the Tijarah context, which was seen from 1) changes in context and the problems raised; 2) the form of constructivist learning and 3) the relationship between learning and the Tijarah context. This shows that in the process of preparing open materials, didactic transposition can occur.